PANDANGAN FORUM UKHUWAH ISLAMIYAH CIREBON TENTANG WAWASAN KEBANGSAAN - Suhanah Suhanah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
The purpose of this research are providing an overview of Forum Ukhuwah Islamiyah profile in Cirebon and its view about the form of NKRI, Pancasila, UUD 1945, and Bhinneka Tunggal Ika related to the ideal state form that they voice out. The scope of this research is to explore and analyze the Forum Ukhuwah Islamiyah views related to four issues as mention above. The main source of the data of this research is observation, in-depth interviews; focus group discussion, literature and document review. The research method used in this study was qualitative research methods.